Parental prenatal representations of the child are related to 18-month-old children's social-emotional competence - Lindstedt, Johanna; Korja, Riikka; Carter, Alice; Pihlaja, Päivi; Ahlqvist-Björkroth, Sari (Routledge, 2025)
Parental representations of the child are linked to positive developmental outcomes in children, but the impact of prenatal representations on early social-emotional development, particularly from fathers, is less understood. This study explores how fathers' and mothers' prenatal representations within two-parent families are associated with early social-emotional development. Prenatal representations of fathers (n = 88) and mothers (n = 92) were assessed between 28 and 32 weeks of gestation using the Working Model of the Child Interview, categorizing them as balanced or nonbalanced. The children's (n = 97; 49.5% girls) social-emotional and behavioral problems and competencies were measured at 18 months using the Brief Infant-Toddler Social and Emotional Assessment. Balanced prenatal representations of both parents were related to higher social-emotional competence in toddlers. However, prenatal representations were not related to social-emotional and behavioral problems. The results highlight the benefits of balanced prenatal representations in promoting early social-emotional competence in children.